Pengaruh Kompensasi dan Kepuasan Kerja terhadap Turnover Intetion pada PT. Wahyu Nusantara Indah Putra Surabaya - Fikry Ardiansyah Pranata; Sulastri Irbayuni (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The problem in this study is still the main priority related to turnover intention. This study aims to determine the effect of compensation and job satisfaction on turnover intention at PT. Wahyu Nusantara Indah Putra Surabaya. The data used is primary data, namely data collected through questionnaires distributed to 47 employees of PT. Wahyu Nusantara Indah Putra Surabaya. The sample used in this study were 47 employees of PT. Wahyu Nusantara Indah Putra Surabaya. This study uses an analytical technique in the form of a Partial Least Square (PLS) model which is a technique to construct a model that can be assumed when there are several factors. The measuring instrument used in this study is the Likert scale. The sampling technique used was saturated sampling technique. Based on the results of research conducted, it shows that the lower the level of compensation received by employees, the higher the turnover intention rate and the lower the level of job satisfaction, the higher the turnover intention. Keywords : Compensation; Job Satisfaction; Turnover Intention